Intensity of Some Diseases Main Features of Cocoa Plants (Theobroma Cacao, L.) in Sebapo Village, Mestong District - Yuza Defitri (Kognitif: Jurnal Pendidikan dan Inovasi Pembelajaran, 2026)
Cocoa is one of the plantation commodities that has a relatively high economic value among other plantation crops and plays an important role as a source of foreign exchange for the country through exports and driving the regional economy, especially in rural areas. To increase cocoa production in Sebapo Village, Mestong District, it is necessary to know the condition of the cocoa plants affected by disease, the percentage and intensity of the disease, and how often they are affected . This information is useful for implementing disease control techniques in cocoa plants. This study aims to find out about the main diseases that attack cocoa plants, such as Fruit Rot Disease, Stem Cancer Disease, and Disease. Vascular Streak Dieback (VSD ) and what is the percentage and intensity of attacks of these diseases. The study was conducted using a simple random sampling method. Plant samples were taken randomly from smallholder cocoa plantations. Data were then collected by counting all healthy and diseased plants to determine the percentage and intensity of diseased plants . Samples of diseased cocoa plants were identified at the Unbari Basic Laboratory. The results of the study show that fruit rot disease caused by fungus Phytopthora palmivora in Sebapo village the percentage of attack was 33.33% and the intensity of attack was 14.57%, stem cancer disease caused by Phytopthora palmivora fungus the percentage of attack was 26.66% and the intensity of attack was 12.96%, Vascular Streak Dieback (VSD) disease the percentage of attack was 15% and the intensity of attack was 09.66%.